Dead wrong - Jance, Judith A. (New York : William Morrow, 2006)
As if juggling a family, including the impending birth of a second child, a career and a staff shortage at the Sheriff's office aren't enough, Sheriff Joanna Brady has to deal with two serious crimes. The first is the dead body of an ex-con who was found in the desert with all his fingers severed. The second is the brutal attack of one of her officers while on unauthorized stakeout. Being a sheriff is what she is and Joanna will stop at nothing to get the job done.
Keywords: Brady, Joanna (Fictitious character) -- Fiction; Policewomen -- Fiction; Sheriffs -- Fiction